واقع وتطوّر إنتاج الزيتون في محافظة اللاذقية دراسة تطبيقية في خلال الفترة 2002-2013 - معروف ثائر (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى دراسة واقع إنتاج الزيتون في محافظة اللاذقية, وذلك من خلال سلسلة زمنية تمتد من عام 2002 لغاية عام 2013, وبالاعتماد على الأرقام القياسية, ومعدلات النمو, والانحدار البسيط, تمّت فيه دراسة واقع وتطوّر إنتاج الزيتون, والمساحات المزروعة, وعدد أشجاره خلال الفترة المدروسة, وكان من أهم نتائج البحث: *إنّ العلاقة بين إنتاج الزيتون والزمن خلال الفترة (2002-2013) هي علاقة طردية وقوية, إذ إنّ 73% من التغيرات الحاصلة في إنتاج الزيتون يفسرها الزمن, والباقي يعود لتأثير عوامل أخرى لم تضمن في النموذج. *إنّ العلاقة بين المساحات المزروعة بالزيتون والزمن خلال الفترة (2002-2013) هي علاقة طردية وقوية جداً, إذ إن ّ 87.3% من التغيرات الحاصلة في المساحات المزروعة بالزيتون يفسرها الزمن, والباقي يعود لتأثير عوامل أخرى لم تضمن في النموذج. *إنّ العلاقة بين عدد أشجار الزيتون والزمن خلال الفترة (2002-2013) هي علاقة طردية وقوية جداً, إذ إن أنّ 89% من التغيرات الحاصلة في أشجار الزيتون يفسرها بالزمن, والباقي يعود لتأثير عوامل أخرى لم تضمن في النموذج. The research aims to study the reality of olive production in the province of Latakia, and of time-series extends from the year 2002 to the year 2013, and based on the indices, growth rates, and simple regression, has been studying the reality and the evolution of olive production, and areas planted with olive trees, and the number of trees olive during the period studied, and it was the most important results: *The relationship between the olive production and the time during the period (2002-2013) is a strong and positive relationship, where 73% of the developments in the production of olive explained by changes of time, and the rest is due to the influence of other factors not included in the model. *The relationship between the cultivated olives space and time during the period (2002-2013) is a very positive and strong relationship, where 87.3% of the developments in the areas cultivated with olives interpret the changes of time, and the rest is due to the influence of other factors not included in the model. *The relationship between the olive trees and the time during the period (2002-2013) is the relationship between positive and very strong, since 89% of the developments in the olive trees explained by changes in time, and the rest is due to the influence of other factors not included in the model.